Guidance of Tram Wheelset Passing Over Obtuse Crossing (Current Problems in Rail Vehicles, 2025)
This paper is concerned to the assessment of a wheelset–track interaction in the obtuse crossing of a tram operation. The analysis contains the two most common cases in terms of a tram track structure – the crossing with the deep grooves in the tram track structure of the Vignol rails and the crossing with the flat grooves. The method of the assessment of a wheelset passing over the obtuse crossing defined in the code UIC 510-2 is used and applied to the tram operation. The analysis of a wheelset-track interaction is performed for the different values of the key dimensional parameters of a wheelset and a track for the purpose of the determination of the basic requirements to ensure the reliable tram wheelset guidance passing over the obtuse crossing.
Keywords: tram; wheelset; rail; flange; guard rail; obtuse crossing; deep groove; flat groove; double frog